2021
DOI: 10.3892/mmr.2021.12149
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA GAS5‑mediated miR‑23a‑3p promotes inflammation and cell apoptosis by targeting TLR4 in a cell model of sepsis

Abstract: Sepsis is a syndrome characterized by organ dysfunction and an abnormal immune response to infection. A growing body of research has shown the importance of long non-coding RNAs (lncRNAs) in tumorigenesis, virus replication, inflammatory injury and other pathological processes. The aim of the present study was to explore the role and potential mechanism of the lncRNA growth arrest-specific 5 (GAS5) in the lipopolysaccharide (LPS)-induced inflammation and apoptosis of THP-1 cells. An in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Sepsis is featured by the extremely high mortality which is regarded as a global health priority by the WHO, therefore, it is urgent to find the biomarker involving the development and progression of sepsis to stratify the patients and individualize their treatment, which might help to improve the prognosis of sepsis patients 1–6 . Previous studies have reported the regulation role of lnc‐GAS5 in sepsis 18,24 . For instance, one study shows lnc‐GAS5‑mediated miR‑23a‑3p promotes inflammation and cell apoptosis by targeting TLR4 in a cell model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sepsis is featured by the extremely high mortality which is regarded as a global health priority by the WHO, therefore, it is urgent to find the biomarker involving the development and progression of sepsis to stratify the patients and individualize their treatment, which might help to improve the prognosis of sepsis patients 1–6 . Previous studies have reported the regulation role of lnc‐GAS5 in sepsis 18,24 . For instance, one study shows lnc‐GAS5‑mediated miR‑23a‑3p promotes inflammation and cell apoptosis by targeting TLR4 in a cell model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Previous studies have reported the regulation role of lnc-GAS5 in sepsis. 18,24 For instance, one study shows lnc-GAS5-mediated miR-23a-3p pro- The lnc-GAS5 has been reported to be involved in regulating macrophage polarization, Treg cell differentiation, and inflammation in various inflammation-related diseases. For instance, in childhood pneumonia, lnc-GAS5 might regulate the Treg/Th17 imbalance by targeting the miR-217/STAT5 axis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations